Math, asked by ff2, 14 days ago

multiply.
(a^2-b^2)(a^2-b^2)​

Answers

Answered by anindyaadhikari13
19

\star\:\:\:\bf\large\underline\blue{Question:-}

  • Multiply ( {a}^{2}  -  {b}^{2} )( {a}^{2}  -  {b}^{2})

\star\:\:\:\bf\large\underline\blue{Solution:-}

( {a}^{2}  -  {b}^{2} )( {a}^{2}  -  {b}^{2})

 = ( {a}^{2}  -  {b}^{2} )^{2}

 =  {a}^{4}  +  {b}^{4} - 2 {a}^{2}   {b}^{2}

\star\:\:\:\bf\large\underline\blue{Answer:-}

  • {a}^{4}  +  {b}^{4} - 2 {a}^{2}   {b}^{2}
Answered by Anonymous
2

Answer:

(a^2-b^2)(a^2-b^2)

= a^2(a^2-b^2)-b^2(a^2-b^2)

= a^4-a^2b^2-a^2b^2+b^4

= a^4-2a^2b^2+b^4

Similar questions